BAYESIAN NETWORK DESIGN FOR A DECISION SUPPORT SYSTEM IN SOUTH ASIAN E-COMMERCE MANAGEMENT - Jamshed, Ammar (International Journal For Research In Advanced Computer Science And Engineering, 2023)
E-commerce is a thriving industry in Pakistan which is the a high population density country connected by air travel and road networks to India and China as well as central Asia thus using advanced computing algorithms allow for examination into effective business practices for managerial commerce via smart technology platforms and using Bayesian model for predictability of consumer purchasing based on behavioral variables in Pakistan serve as foundational support in expansion of smart management of E-commerce in Pakistan and other potential markets of Bangladesh and Sri Lanka with similar behavioral trends.